Indo‐Pacific Sector Dominates Southern Ocean Carbon Outgassing. Issue 7 (30th June 2022) - Prend, Channing J.; Gray, Alison R.; Talley, Lynne D.; Gille, Sarah T.; Haumann, F. Alexander; Johnson, Kenneth S.; Riser, Stephen C.; Rosso, Isabella; Sauvé, Jade; Sarmiento, Jorge L.
Abstract: The Southern Ocean modulates the climate system by exchanging heat and carbon dioxide (CO2 ) between the atmosphere and deep ocean. While this region plays an outsized role in the global oceanic anthropogenic carbon uptake, CO2 is also released to the atmosphere across large swaths of the Antarctic Circumpolar Current (ACC). Southern Ocean outgassing has long been attributed to remineralized carbon from upwelled deep water, but the precise mechanisms by which this water reaches the surface are not well constrained from observations. Using data from a novel array of autonomous biogeochemical profiling floats, we examine Southern Ocean air‐sea CO2 fluxes and the pathways that transfer carbon from the ocean interior into the mixed layer where air‐sea exchange occurs. These float‐based flux estimates of unprecedented spatial resolution indicate that carbon outgassing occurs predominantly in the Indo‐Pacific sector of the ACC due to variations in the mean surface ocean partial pressure of CO2 ( p CO2 ). We show that this zonal asymmetry in surface p CO2, and consequently air‐sea carbon fluxes, stems primarily from regional variability in the mixed‐layer entrainment of upwelled carbon‐rich deep water. These results suggest that a sustained circumpolar observing system is crucial to monitor future changes in oceanic carbon release and uptake. Plain Language Summary: The Southern Ocean, which surrounds Antarctica, helps regulate the global climate system by sequestering atmospheric heat and carbon dioxide (CO2 ) in the deep ocean. Although this region makes a significant contribution to the total oceanic carbon uptake, there are also locations in the Southern Ocean where CO2 is released back into the atmosphere. Understanding what controls these patterns of air‐sea carbon exchange is necessary to improve climate models and prepare for the effects of climate change. However, studying the Southern Ocean carbon cycle is difficult due to the lack of observations from this remote environment. Here, we use new data collected by autonomous biogeochemical floats to examine air‐sea carbon fluxes throughout the Southern Ocean. We find that ocean carbon release occurs preferentially in the Indo‐Pacific sector of the Southern Ocean due to systematic differences between basins in the transport of subsurface carbon from the deep ocean into the mixed layer—the portion of the upper ocean that is in direct contact with the atmosphere. These results suggest that collecting data from all sectors of the Southern Ocean is crucial to monitor future changes in the ocean carbon sink. Key Points: Autonomous biogeochemical floats reveal that carbon outgassing occurs predominantly in the Indo‐Pacific sector of the Southern Ocean Asymmetry in carbon outgassing is driven by systematic interbasin variations in the mixed‐layer entrainment of carbon‐rich deep water Expanded data coverage, particularly circumpolar sampling, is necessary to accurately capture Southern Ocean carbon sink variability